2023
DOI: 10.1007/s11356-022-25001-5
|View full text |Cite
|
Sign up to set email alerts
|

Do different types of carbon mitigation regulations have heterogeneous effects on innovation quality?

Abstract: Carbon peak and carbon neutralization as a global mission cannot be completed without systematically designed carbon mitigation regulations. In order to achieve the carbon emission reduction as formulated in the Paris Agreement and fulfill the promises made at the United Nations General Assembly, the Chinese government has promulgated various types of regulations to curb carbon emission with the hope of realizing the Porter effect. Selecting low-carbon pilot cities and carbon emission trading schema as the res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…One viewpoint posits that the CETM promotes substantial innovation. Employing a quasinatural experimental research method, Xu and Cui (2020) and Yang and Xu (2023) showed that the CETM promotes substantial innovation in pilot regions. Conversely, another perspective argues that the CETM has minimal to no influence.…”
Section: Green Technology Innovation (Gti) Embodies Both "Innovation"mentioning
confidence: 99%
“…One viewpoint posits that the CETM promotes substantial innovation. Employing a quasinatural experimental research method, Xu and Cui (2020) and Yang and Xu (2023) showed that the CETM promotes substantial innovation in pilot regions. Conversely, another perspective argues that the CETM has minimal to no influence.…”
Section: Green Technology Innovation (Gti) Embodies Both "Innovation"mentioning
confidence: 99%